2016
DOI: 10.1021/jacs.6b07334
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probes for Single-Step Detection and Proteomic Profiling of Histone Deacetylases

Abstract: Histone deacetylases (HDACs) play important roles in regulating various physiological and pathological processes. Developing fluorescent probes capable of detecting HDAC activity can help further elucidate the roles of HDACs in biology. In this study, we first developed a set of activity-based fluorescent probes by incorporating the Kac residue and the O-NBD group. Upon enzymatic removal of the acetyl group in the Kac residue, the released free amine reacted intramolecularly with the O-NBD moiety, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…To assess the ability of peptide PD3-I to label PDZ DRGS3 in a complex proteome environment, 293 T cell lysates (300 mg) were spiked with PDZ DRGS3 (10 mg), and then treated with 50 mM FAM labeled peptide PD3-I as shown in Fig. 3E, referring to the work of Sun et al 45 The gel data showed a clear single uorescence band with the right molecular weight indicating a clean and selective conjugation of peptide PD3-I to PDZ DRGS3 . The successful conjugation was further conrmed by a pull down assay using Ni-NTA agarose beads as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the ability of peptide PD3-I to label PDZ DRGS3 in a complex proteome environment, 293 T cell lysates (300 mg) were spiked with PDZ DRGS3 (10 mg), and then treated with 50 mM FAM labeled peptide PD3-I as shown in Fig. 3E, referring to the work of Sun et al 45 The gel data showed a clear single uorescence band with the right molecular weight indicating a clean and selective conjugation of peptide PD3-I to PDZ DRGS3 . The successful conjugation was further conrmed by a pull down assay using Ni-NTA agarose beads as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other recently developed substrates allow deacetylation to be monitored in a single-step. 24,50,51 For some of these substrates, the dyes are positioned further away from the acetylated lysine than for the AMC substrates; 52,53 however, it will be important to determine how the configuration of these substrates affects KDAC activity. An assumption that AMC or other fluorophores might mimic large non-polar residues after the acetyllysine is clearly incorrect, as tryptophan in the +1 position causes distinctly different activity effects than AMC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently,X ie and co-workers developed bifunctional probe 37 that was capable of monitoring HDAC activity,a s well as identifying cellular targets through tandemP AL ( Figure 10). [27] In the presence of HDACs, the appendant Nacetyl group is deacetylated to form the free amine, which undergoes an intramolecular substitution reactionw itht he O-ni-trobenzoxadiazole (NBD) to form the N-NBD as ah ighly fluorescent species. [59] They demonstrated the ability of 37 to effectively label SIRT1 and SIRT2 in ac omplex proteomic environment as well as its efficacy to differentiate between epigenetic eraser BRD4-1 and readerS IRT2 in cell culture.…”
Section: Development Of Minimalist Pallinkersmentioning
confidence: 99%